Peningkatan Hasil Belajar IPAS Siswa Sekolah Dasar melalui Model Cooperative Learning Berbantuan Talking Stick Terintegrasi Deep Learning - Emiliana M. G. Moron; Eufrasia J. S. Wedo; Bintang E. P. Sabah; Graziana M. J. Sogen; Serlyana Leo; Daniel W. Fointuna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science and Social Studies (Ilmu Pengetahuan Alam dan Sosial / IPAS) learning in elementary schools still faces challenges in the form of low student participation and learning outcomes due to the dominance of conventional teaching methods. This study aims to analyze the effect of implementing the cooperative learning model assisted by the talking stick technique, supported by interactive PowerPoint media and integrated with a deep learning approach, on the IPAS learning outcomes of third-grade students on the topic of symbiosis. The deep learning approach was applied through collaborative learning activities that encouraged active student engagement and conceptual understanding. This study employed a quantitative approach with a one group pretest–posttest design. The research subjects consisted of 17 third-grade students at SDI Bertingkat Perumnas 3. The research instruments included a pretest and posttest consisting of 20 multiple-choice questions that had been validated by experts, as well as observation sheets assessing students’ attitudes and skills. Data were analyzed using a paired sample t-test. The results showed a statistically significant improvement in students’ IPAS learning outcomes (p < 0.05) with a very large effect size (Cohen’s d = 1.694). Therefore, the implementation of the cooperative learning model assisted by the talking stick technique and integrated with a deep learning approach is effective in improving IPAS learning outcomes in elementary schools.